The violence of hate: understanding harmful forms of bias and bigotry - Levin, Jack (Rowman & Littlefield, 2017)
Perspectives on hate and violence -- Hate crimes -- A typology of hate -- The benefits of bigotry -- The production of rebels, deviants, and other decent people